Continuous formation of a seed layer and vertical ZnO nanowire arrays enabled by tailored reaction kinetics in a microreactor. Issue 44 (27th October 2016) - Choi, Chang-Ho; Levin, Janssen Ballard; Chang, Chih-hung
Abstract : The aim of this study is to reveal the growth mechanism of ZnO NW arrays in a continuous flow microreactor system and tune the dimensions of ZnO NWs on the basis of understanding the growth mechanism. Abstract : ZnO nanowires (NWs) are gaining widespread popularity due to their many unique physical and chemical properties. The hydrothermal process is the most commonly used approach to prepare vertical ZnO NW arrays. Its fundamental issues are the rather slow deposition rate and the variation of reactant concentrations as a function of time. In this study, we employed a continuous flow microreactor and deposition system to prepare both a ZnO seed layer and vertical ZnO NW arrays continuously by simply tuning the flow rate of reactant solutions. The change in flow rate allows reaction kinetics to be selectively tuned, resulting in the generation of molecular zinc species and colloidal ZnO nanocrystals at a high and low flow rate, respectively. The molecular zinc species constitute the seed layer at the high flow rate, and subsequently the colloidal ZnO nanocrystals contribute to the growth of ZnO NWs at the low flow rate. Since the direct delivery of the controlled building blocks on the substrate prevents the formation of homogeneously induced ZnO particles, we were able to obtain highly uniform ZnO NW arrays, with a growth rate as fast as 240 nm min −1, which is significantly higher than typical growth rates from gas-phase or batch hydrothermal processes. Based on the growth mechanism study, the dimensions of the vertical ZnO NW arrays were varied, leading to an aspect ratio of the NWs up to 23. The advantages of our system were highlighted by preparing a high-quality heterogeneous surface having both hydrophilic and hydrophobic nature on one substrate. These results demonstrate the capability of the continuous flow microreactor and deposition system in efficiently preparing functional vertical ZnO NW arrays.